Finite element analysis on buckling of rectangular composite plates in compression - Nyo, Darren Jie Jun (Nanyang Technological University, 2022)
This project aims to investigate the buckling of Rectangular Composite plates using Finite Element Analysis, and hence determining an estimate of its ultimate compressive load. The finite element programme ANSYS (academic version 21.0) was utilised for the purpose of this study. The scope of work includes the effect of coupling between the layers of the laminate, and hence will investigate the difference of ultimate compressive loads between different types of laminae, namely anti- and symmetric, cross- and angle-ply composites. During the course of the study, the simulation times were a big challenge due to the small element sizes present in the model on top of many different ANSYS errors that appear during simulation. With increasing usage of composite materials in our everyday lives, it is important to study the critical buckling loads of laminated plate structures with different stacking sequence to ensure the buckling strength and reduce the possibility of failures in important support structures.